Difficulties Of Teaching Biology In The Middle School From a Point Of View Its Teachers Are In Wasit Governorate (Journal of the College of Basic Education, 2024)
The study aimed to identify the difficulties of teaching biology in the preparatory stage from the point of view of its teachers in Wasit Governorate. The researcher used the descriptive approach - survey studies. The study population included male and female biology teachers for the preparatory stage in schools affiliated with the General Directorate of Education of Wasit Governorate and in education departments. Affiliated to the districts of Essaouira, Azizia, and Zubaidiyeh, the research community consisted of (127) biology teachers and schools, while the research sample consisted of (69) biology teachers and schools who were chosen by a simple random method. The researcher prepared the research tool, which is a questionnaire of difficulties, which consisted of (54) distributed items. On eight areas, and after applying the questionnaire to the research sample and extracting the results using the statistical package (spss), the results showed that the difficulties of teaching the subject Biology in the preparatory stage, from the point of view of its teachers in Wasit Governorate, reached (35) items of high difficulty in the questionnaire’s (54) items distributed among its eight areas. The area of teaching methods, the area of the teacher, and the area of content had the highest difficulty, followed by the other areas in varying proportions. In light of the research results, the researcher recommended several recommendations, including: - The need to familiarize biology teachers with the general and specific objectives of the different levels and classifications of biology, as well as interest in introducing them to development courses using modern teaching methods and keeping pace with global development in this field.